Issue Cover. (22nd February 2022) - Gerussi, Alessio; Verda, Damiano; Bernasconi, Davide Paolo; Carbone, Marco; Komori, Atsumasa; Abe, Masanori; Inao, Mie; Namisaki, Tadashi; Mochida, Satoshi; Yoshiji, Hitoshi; Hirschfield, Gideon; Lindor, Keith; et al.
Abstract : The cover image is based on the Original Article Machine learning in primary biliary cholangitis: A novel approach for risk stratification by Alessio Gerussi et al., https://doi.org/10.1111/liv.15141 .